Changes in dental practice in times of COVID-19: review and recommendations for dental health care - Manuela Gonçalves de Souza e Silva SILVEIRA; Matheus dos Santos FERNANDEZ; Thais Freitas Formozo TILLMANN; Júlia Freire DANIGNO; Mariana Silveira ECHEVERRIA; Alexandre Emidio Ribeiro SILVA (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT The aim of this article was to discuss biosafety measures described in the main protocols for minimizing the risk of COVID-19 transmission during dental care. COVID-19 appeared in China in late 2019 and quickly spread to other countries. Factors inherent to dental practice, such as proximity to the patient, transmission through saliva and breath, and the generation of aerosols during procedures, place the dental team at the top of the list among the most vulnerable healthcare providers. Health authorities initially recommended only maintaining urgent and emergency care and suspending elective dental procedures. Currently, elective care is gradually being resumed and requires numerous adjustments to the environment and professional routine in terms of biosafety. Several methods had been recommended to prevent the spread of other infectious diseases prior to the outbreak of COVID-19. However, further modifications are needed for the waiting room, patient screening and flow, procedures, garments, and even in dental office itself. Thus, dental professionals need to be prepared to adopt the new recommendations in order to reduce the chance of disease transmission.